Adapting Practical Aesthetics to the performance animation process. Issue 1 (1st December 2016) - Mohr, Steven; Carter, Chris
The relevance of acting theory to character animation was recognized early in the history of animation. In the 1930s, Disney animators studied the performances of actors to improve the quality of their animation and this tradition has continued into contemporary practices. The following article is derived from a recent practice-led study, which sought to adapt David Mamet and William H. Macy's acting technique, Practical Aesthetics, to 3D computer animation practice. Reflecting upon a series of short character animation studies, this article shows how the animator can create authentic and therefore more believable character performances via the techniques of Practical Aesthetics.